Adhesion molecule cross‐linking and cytokine exposure modulate IgE‐ and non‐IgE‐dependent basophil activation. Issue 1 (29th October 2020) - Kalm, Frida; Mansouri, Ladan; Russom, Aman; Lundahl, Joachim; Nopp, Anna
Summary: Basophils are known for their role in allergic inflammation, which makes them suitable targets in allergy diagnostics such as the basophil activation test (BAT) and the microfluidic immunoaffinity basophil activation test (miBAT). Beside their role in allergy, basophils have an immune modulatory role in both innate immunity and adaptive immunity. To accomplish this mission, basophils depend on the capability to migrate from blood to extravascular tissues, which includes interactions with endothelial cells, extracellular matrix and soluble mediators. Their receptor repertoire is well known, but less is known how these receptor–ligand interactions impact the degranulation process and the responsiveness to subsequent activation. As the consequences of these interactions are crucial to fully appreciate the role of basophils in immune modulation and to enable optimization of the miBAT, we explored how basophil activation status is regulated by cytokines and cross‐linking of adhesion molecules. The expression of adhesion molecules and activation markers on basophils from healthy blood donors was analysed by flow cytometry. Cross‐linking of CD203c, CD62L, CD11b and CD49d induced a significant upregulation of CD63 and CD203c. To mimic in vivo conditions, valid also for miBAT, CD62L and CD49d were cross‐linked followed by IgE‐dependent activation (anti‐IgE), which caused a reduced CD63 expression compared with anti‐IgE activation only. IL‐3 and IL‐33 priming caused increased CD63 expression after IgE‐independent activation (fMLP). Together, our data suggest that mechanisms operational both in the microfluidic chip and in vivo during basophil adhesion may impact basophil anaphylactic and piecemeal degranulation procedures and hence their immune regulatory function. Abstract : Basophil adhesion and activation are important steps for the basophil immune modulatory functions and can be investigated with flow cytometry and microfluidics (miBAT). Cross‐linking of CD203c and the adhesion molecule CD62L, which mimics both adhesion in vivo and capture in miBAT, has a regulator effect on IgE‐mediated (anti‐IgE) basophil degranulation, by reducing the CD63 expression compared with anti‐IgE activation only. In addition, IL‐3 and IL‐33 enhance the CD63 expression on basophils after IgE‐independent (fMLP) activation compared with fMLP activation only.